Differential Growth of Francisella tularensis, Which Alters Expression of Virulence Factors, Dominant Antigens, and Surface-Carbohydrate Synthases, Governs the Apparent Virulence of Ft SchuS4 to Immunized Animals - Holland, Kristen M.; Rosa, Sarah J.; Kristjansdottir, Kolbrun; Wolfgeher, Donald; Franz, Brian J.; Zarrella, Tiffany M.; Kumar, Sudeep; Sunagar, Raju; Singh, Anju; Bakshi, Chandra S.; Namjoshi, Prachi; Barry, Eileen M.; et al. (Frontiers in Microbiology, 2017)
The gram-negative bacterium Francisella tularensis (Ft) is both a potential biological weapon and a naturally occurring microbe that survives in arthropods, fresh water amoeba, and mammals with distinct phenotypes in various environments. Previously, we used a number of measurements to characterize Ft grown in Brain-Heart Infusion (BHI) broth as 1) more similar to infection-derived bacteria, and 2) slightly more virulent in naïve animals, compared to Ft grown in Mueller Hinton Broth (MHB). In these studies we observed that the free amino acids in MHB repress expression of select Ft virulence factors by an unknown mechanism. Here, we tested the hypotheses that Ft grown in BHI (BHI-Ft) accurately displays a full protein composition more similar to that reported for infection-derived Ft and that this similarity would make BHI-Ft more susceptible to pre-existing, vaccine-induced immunity than MHB-Ft. We performed comprehensive proteomic analysis of Ft grown in MHB, BHI, and BHI supplemented with casamino acids (BCA) and compared our findings to published “omics” data derived from Ft grown in vivo. Based on the abundance of ~1000 proteins, the fingerprint of BHI-Ft is one of nutrient-deprived bacteria that - through induction of a stringent-starvation-like response - have induced the FevR regulon for expression of the bacterium’s virulence factors, immuno-dominant antigens, and surface-carbohydrate synthases. To test the notion that increased abundance of dominant antigens expressed by BHI-Ft would render these bacteria more susceptible to pre-existing, vaccine-induced immunity, we employed a battery of LVS-vaccination and S4-challenge protocols using MHB- and BHI-grown Ft S4. Contrary to our hypothesis, these experiments reveal that LVS-immunization provides a barrier to infection that is significantly more effective against an MHB-S4 challenge than a BHI-S4 challenge. The differences in apparent virulence to immunized mice are profoundly greater than those observed with primary infection of naïve mice. Our findings suggest that tularemia vaccination studies should be critically evaluated in regard to the growth conditions of the challenge agent.